2009
DOI: 10.1091/mbc.e09-03-0207
|View full text |Cite
|
Sign up to set email alerts
|

Pob1 Participates in the Cdc42 Regulation of Fission Yeast Actin Cytoskeleton

Abstract: Rho GTPases regulate the actin cytoskeleton in all eukaryotes. Fission yeast Cdc42 is involved in actin cable assembly and formin For3 regulation. We isolated cdc42-879 as a thermosensitive strain with actin cable and For3 localization defects. In a multicopy suppressor screening, we identified pob1 ؉ as suppressor of cdc42-879 thermosensitivity. Pob1 overexpression also partially restores actin cables and localization of For3 in the mutant strain. Pob1 interacts with Cdc42 and this GTPase regulates Pob1 local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0
33

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 48 publications
5
64
0
33
Order By: Relevance
“…S5 F-H), similar to oscillations seen in sla2Δ. CRIB-GFP dynamics could not be determined in this mutant, because levels were dramatically decreased (30). However, the detection of Knk1 oscillation despite a reduction of active Cdc42 in cell tips strongly suggests that Knk1 oscillations are not driven by Cdc42 dynamics.…”
Section: Knk1 Localization At the Cell Tip Is Independent Of Mts And mentioning
confidence: 75%
“…S5 F-H), similar to oscillations seen in sla2Δ. CRIB-GFP dynamics could not be determined in this mutant, because levels were dramatically decreased (30). However, the detection of Knk1 oscillation despite a reduction of active Cdc42 in cell tips strongly suggests that Knk1 oscillations are not driven by Cdc42 dynamics.…”
Section: Knk1 Localization At the Cell Tip Is Independent Of Mts And mentioning
confidence: 75%
“…Our attempts to clone the corresponding genes led to the isolation of numerous dosage suppressors (Table 4), in addition to the gene (rgf3) that actually contains the s44 mutation. Given what is known about the functions of Rho1, the Rho-GEFs, Pck2, and Pob1 in S. pombe (see Introduction; Toya et al 1999;Rincó n et al 2009) and about the well-studied cell-wall-integrity pathway in S. cerevisiae (Levin 2005), it seems clear that the seven genes identified as dosage suppressors all represent components of a similar pathway in S. pombe, as also described, in part, in several other recent studies (Madrid et al 2006(Madrid et al , 2007Barba et al 2008; and references cited therein). In this model, Wsc1 is a sensor of cell-wall damage that works through one or more of the Rho-GEFs Rgf1, Rgf2, and Rgf3 to activate Rho1.…”
Section: Discussionmentioning
confidence: 99%
“…It is also found that downregulation of REPS2 is accompanied by upregulation of NF-kB activity during progression of prostate cancer from androgen-dependent to androgen-independent growth, and that NF-kB may promote cell proliferation through interacting with the EH domain of REPS2 (Penninkhof et al, 2004). In addition, REPS2 may function to keep RalBP1 cytosolic where it displays a GAP activity towards Rac1 and Cdc42 to signal cell survival so that overexpression of REPS2 may lead to a strong inhibition of Rac1 and Cdc42 signalling, which may consequently result in the attendant induction of apoptosis (Jullien-Flores et al, 1995;Joneson et al, 1999;Rincon et al, 2009). Above molecular mechanisms may provide the theoretical basis of REPS2 for participating in the the progression of ESCC, but that need further research to testify in future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…We have already mentioned the overexpression of REPS2 may lead to a strong inhibition of Rac1 and Cdc42 signalling that is required for the actin cytoskeleton organization and cell morphogenesis. Rac1 and Cdc42, two members of the Rho family of small GTPases, are all involved in cell transformation, survival, proliferation, invasion and metastasis of human cancer cells (Rincon et al, 2009;Bashir et al, 2010;Feng et al, 2012). Overexpression of Rac1 and Cdc42 have been reported in several types of human cancer including esophageal cancer (Bashir et al, 2010;Feng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%